Relative permeability variations during low salinity water flooding in carbonate rocks with different mineral compositions. Issue 2 (28th January 2020) - Su, Wenbo; Liu, Yuetian; Gao, Ziang; Yang, Li; Yang, Renfeng; Mcharo, Wilson; Tang, Ruoyu
Abstract: This article presents an extensive relative permeability study for low salinity water flooding (LSWF) in minerally different carbonate rocks. The experiments were performed with unsteady state method using artificial cores, crude oil and synthetic brines. The effect of water salinity and rock composition on relative permeability was obtained. The results show that the oil (water) relative permeability increases (decreases) first and then decreases (increases) with the decrease of the salinity of brines. Actually, there exists an optimal salinity (2384.6 mg/L) which maximizes the oil relative permeability and minimizes water relative permeability. When low salinity water is kept the same, the higher calcite content in the carbonate rock, the bigger oil relative permeability and the smaller water relative permeability will be. GRAPHICAL ABSTRACT: